2000
DOI: 10.1039/b003124k
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of nitrogen dioxide passive diffusion tubes for ambient measurement: in situ properties of the triethanolamine absorbent

Abstract: Factors concerning NO2 uptake by the absorbent triethanolamine (TEA) in NO2 diffusion tubes are examined. Although the nominal freezing point of TEA is 17.9-21.2 degrees C, we show that, for a range of aqueous TEA solutions (0-20%, H2O), no freezing occurs even at -10 degrees C. Therefore NO2 collection efficiency is unlikely to be impaired by low temperature exposure. The recovery of TEA from the meshes of exposed samplers is determined as approximately 98%, even after 42 days, showing that the stability in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 15 publications
6
39
0
Order By: Relevance
“…In this study, all the samplers were co-located at the same atmospheric research stations in Singapore, the effects from meteorology were minimized by specially designed protective screens and shelters. The factors such as different materials of the tubes, non-consistent diffusion paths and areas for different samplers and various absorbent solutions applied may result in the variations of the measurement accuracy (Glasius et al, 1999;Kirby et al, 2000;Vardoulakis et al, 2009). In addition, it should be noted that the biases derived are associated with both sampling and analytical methods.…”
Section: Passive Sampling For Two Round Robin Tests In Singaporementioning
confidence: 99%
“…In this study, all the samplers were co-located at the same atmospheric research stations in Singapore, the effects from meteorology were minimized by specially designed protective screens and shelters. The factors such as different materials of the tubes, non-consistent diffusion paths and areas for different samplers and various absorbent solutions applied may result in the variations of the measurement accuracy (Glasius et al, 1999;Kirby et al, 2000;Vardoulakis et al, 2009). In addition, it should be noted that the biases derived are associated with both sampling and analytical methods.…”
Section: Passive Sampling For Two Round Robin Tests In Singaporementioning
confidence: 99%
“…However, its optimum volume and concentrations still need to be optimized for each sampling condition. Kirby et al (2000) suggested that the amount of the TEA used should be 10 or 20 % in de-ionized water and its volume should be in the range of 25-50 lL. Under these conditions, the passive samplers obtained from Gradko International (7.1 cm length and 1.1 cm i.d.)…”
Section: Introductionmentioning
confidence: 99%
“…The extract was then completed with Saltzman reagent which colorimetrically determines NO 2 -. Preparation of the Saltzman reagent may be varied; for instance, the ratio of sulfanilamide to NEDA can be 20:1 (Kirby et al 2000;Royset 1998) or 10:1 (Ahmad et al 2011). The colorimetric method is based on the Saltzman reagent with spectrophotometry as the most common method for determining NO 2 (Ahmad et al 2011;Campos et al 2010;Ozden and Dogeroglu 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The over read in diffusion tubes may be attributed to different factors such as the shortening of the diffusive length by wind because of the open end of the sampler, blocking of UV light resulting in reduced NO 2 photolysis in the tube and the effects of PAN. The poor extraction efficiency (incomplete extraction of absorbed NO 2 during analysis) may be an important reason for the under estimation of NO 2 and also, low sampling efficiency resulting from insufficient loading of TEA during the tube preparation was provided as another important reason by Kirby et al (2000) for the underread of NO 2 . Kirby et al (2000) examined the factors concerning NO 2 uptake rate by TEA and in situ behaviour of this absorbent.…”
Section: No 2 Passive Samplingmentioning
confidence: 99%